Effect of Sarwala operation on the performance and yield of some sorghum cultivars in rainfed areas - fadlalmola, meera; Yousif, Lotfie (Gezira Journal of Agricultural Science, 2013)
Field experiments were conducted in the mechanized rainfed areas of Gedarif State during two consecutive seasons, 2001 and 2002, in one site in the first season and two sites in the second season. The objective was to study the effect of Sarwala operation on the performance of some sorghum cultivars, namely, Gadambalia Bloom, Um Baneen, Arfa Gadamak, Tabut and Wad Ahmed. Seeds were sown at the rate of 7.5 kg/fed in both seasons. However, in the second season, additional sowing was done at the rate of 3.2 kg/fed for hand weeding. A randomized complete block design with four replicates was used. Sowing was carried out during the third and the fourth week of July for the first and the second seasons, respectively. Sarwala operation was done after 25-30 days from crop emergence. Crop plants were counted immediately before Sarwala, two weeks later and at harvest.  Percent reductions in plants as well as the number of heads and grain yield were determined. Results showed that plant population before Sarwala depended on seed size. Sarwala significantly reduced sorghum stand. Irrespective to sorghum cultivars, Sarwala significantly increased grain yield compared to hand weeding; however, Tabut cultivar resulted in the lowest yield. Moreover, the results showed that Sarwala increased rain efficiency. The overall average rain efficiency for Sarwala was 2.54 kg/fed/mm while it was 1.63 kg/fed/mm for the hand weeding. The productivity of sorghum cultivars Gadambalia Bloom, Um Baneen, Arfa Gadamak and Wad Ahmed increased significantly with Sarwala compared to hand weeding in the mechanized rainfed areas of eastern Sudan. نفذت هذه التجارب الحقلية في مناطق الزراعة المطرية الآلية بولاية القضارف خلال موسمين متتاليين 2001 و 2002م، في موقع واحد في الموسم الأول و موقعين في الموسم الثاني. يهدف هذا البحث لدراسة تأثير عملية السرولة على أداء وإنتاجية بعض أصناف الذرة الرفيعة الآتية: زهرة القدمبلية، أم بنين، أرفع قدمك، طابت و ود أحمد. زرعت الأصناف في الموسمين بمعدل بذور 7.5كجم/الفدان بالإضافة لزراعتها بمعدل 3.2 كجم/الفدان كشاهد (بدون سرولة – عزيق يدوي) في الموسم الثاني. استخدم في التجربة تصميم القطاعات العشوائية الكاملة بأربعة مكررات. تمت الزراعة خلال الأسبوع الثالث والرابع من شهر يوليو لكل من الموسم الأول والثاني على التوالي. أجريت عملية السرولة بعد مضي 25 – 30 يوم من الإنبات. تم حساب عدد النباتات في المتر المربع ثلاث مرات قبل السرولة مباشرة، بعد مضي 15 يوم من السرولة وعند الحصاد. كما تم تحديد نسبة النقصان في عدد النباتات، بالإضافة لعدد القناديل والإنتاجية. أوضحت النتائج أن عدد النباتات قبل السرولة (عند التأسيس) يعتمد على حجم البذرة. السرولة أدت إلى تخفيض عدد النباتات بصورة معنوية. زادت السرولة الإنتاجية معنوياً مقارنة  بالشاهد بغض النظر عن الصنف ، بيد أن الصنف طابت أعطى أقل إنتاجية. كما أوضحت النتائج أن السرولة زادت من فاعلية الأمطار، فالمتوسط العام لإنتاجية الأمطار كان 2.54 كجم/الفدان/ م م في حالة السرولة بينما كان 1.63 كجم/الفدان/م م في حالة الشاهد. زادت إنتاجية أصناف الذرة الرفيعة زهرة القدمبلية، أم بنين، أرفع قدمك و ود أحمد معنويا مع السرولة مقارنة بالعزيق اليدوي في مناطق الزراعة المطرية الآلية بشرق السودان.